Puncak Pato Sebagai Destinasi Wisata Alam Sumatera Barat - Meria Eliza; Rosta Minawati; Syafriandi Syafriandi (Pascasarjana Institut Seni Indonesia Padang Panjang, 2023)
Puncak Pato, West Sumatra, is a tourist destination located on the border of Sungayang and Lintau. Puncak Pato as a tourism destination has natural and cultural potential. It also has historical meaning in Minangkabau for uniting indigenous peoples and religions known as the